Which factors to induce hearing loss in professional musicians? Extensive literature review and histopathology findings can answer it. (3rd April 2017) - Di Stadio, A.
Abstract: Objective: To evaluate the determining factors of noise-induced sensorineural hearing loss (SNHL) in professional musicians (PMs). Methods: An extensive review using Pubmed, Medscape and Google scholar research was performed and studies with the following keywords were selected: 'hearing loss, tinnitus, hyperacusis, music, classical music, rock music, pop music, musicians, orchestra, music student, professional musician, non-professional musician, music exposure and temporary hearing loss'. A histopathology study from individuals who during life were musician in orchestra was described. Results: Eighty to ninety per cent of PMs are affected from noise-induced SNHL at 3000–8000 Hz frequencies. The range of the frequency of SNHL was correlated with the frequency of the specific frequency of the musical instrument and to the sound intensity which they were exposed. The two temporal bones studied, showed a severely loss hair cells at the basal turn of both cochleae and moderate loss of hair cells in medial and apical turn. Conclusion: The review and the results of the temporal bones (TBs) findings show that the intensity and frequency range are the more relevant factors causing noise-induced high frequency SNHL. The time exposed to sound, instead, can impact the low frequency range as supported by temporal bone results.